2021
DOI: 10.1080/1533256x.2021.1933850
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Patients’ Perceptions of Residential Substance Use Treatment. Is Drop Out a Deliberate or Impulsive Act?

Abstract: The underlying mechanisms of drop out in residential substance use disorder (SUD) treatment were investigated from the users' perspective to identify what impacts their drop-out. A survey-based design was used in this study of patients who had decided to drop-out from residential SUD treatment with a therapeutic community approach. The survey included items such as patient satisfaction, psychological burden, and treatment-related factors such as staff competence. We found a high psychological burden among the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 89 publications
0
2
0
Order By: Relevance
“…Further, should a psychedelic-assisted approach for CUD gain sufficient scientific and regulatory support, the cannabis use-expectancy relationship may allow for the consideration of additional treatment options for clients who exhibit low treatment acceptability for existing SUD treatments (as these may involve aspects that are impractical, cost prohibitive, or associated with high discontinuation rates for various clinical subpopulations; Gaston et al, 2010;López-Goñi et al, 2008;Nash, 2020;Ormbostad et al, 2021;Ravndal et al, 2005). This associaton could be similarly clinically relevant should a psychedelic-assisted therapy gain approval for other conditions that are commonly comorbid with cannabis use disorder (e.g., depression, anxiety; Onaemo et al, 2021), which seems more likely.…”
Section: Implications For Psychedelic Practicementioning
confidence: 99%
“…Further, should a psychedelic-assisted approach for CUD gain sufficient scientific and regulatory support, the cannabis use-expectancy relationship may allow for the consideration of additional treatment options for clients who exhibit low treatment acceptability for existing SUD treatments (as these may involve aspects that are impractical, cost prohibitive, or associated with high discontinuation rates for various clinical subpopulations; Gaston et al, 2010;López-Goñi et al, 2008;Nash, 2020;Ormbostad et al, 2021;Ravndal et al, 2005). This associaton could be similarly clinically relevant should a psychedelic-assisted therapy gain approval for other conditions that are commonly comorbid with cannabis use disorder (e.g., depression, anxiety; Onaemo et al, 2021), which seems more likely.…”
Section: Implications For Psychedelic Practicementioning
confidence: 99%
“…The treatment-related factors that patients reported as being difficult included group therapy, the work structure, sharing accommodations with other patients, and not having access to clinical staff. 60 …”
Section: Introductionmentioning
confidence: 99%
“…57 Recent research points to psychological factors and psychological distress as important factors in predicting dropout. 16,[58][59][60][61] Research has found associations between psychological stress and retention through the use of questionnaires that capture stress levels, such as the Symptom of Stress 58 inventory and Hopkins Symptom Checklist. 54,58,59 In a study from 2021, 60 Ormbostad et al investigated whether dropout was a deliberate or impulsive act.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations